Diamond non-stick surface and cooking utensil

By forming a metal bonding layer on the diamond non-stick surface and filling gap filler, combined with brazing and non-stick coating technology, the problems of existing diamond non-stick surface non-stickness and insufficient bonding strength are solved, and higher non-stickness are achieved. Touch and stability.

CN119259410APending Publication Date: 2025-01-07ONE WORLD INT CO LTD(CN)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310784151.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The non-stickness of existing diamond non-stick surfaces and the insufficient bonding strength of diamond particles to the substrate make the ingredients easily stick to the gaps and the surface of the particles, and the brittleness of the adhesive causes the particles to fall off.

Method used

The metal bonding layer and diamond crystal are formed on the metal substrate, and the gap filler is filled in the gap, the diamond crystal is bonded by brazing, and the carbide is formed using active brazing alloy containing chromium or titanium to enhance the binding force. Octahedral diamond crystals and fluorocarbon resins are non-stick coatings to improve non-stickness.

Benefits of technology

It significantly improves the non-stickness and bonding strength of the diamond's non-stick surface, prevents the ingredients from sticking, enhances the scratch resistance of diamond particles, and ensures that they do not fall off under high mechanical stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259410A_ABST
    Figure CN119259410A_ABST
Patent Text Reader

Abstract

The invention provides a diamond non-stick surface and a cooking utensil. The diamond non-stick surface is provided with a metal base material and a diamond non-stick surface layer, the diamond non-stick surface layer is attached to the metal base material and comprises a metal bonding layer, a plurality of diamond crystals and gap filler, the diamond crystals are bonded to the metal base material through the metal bonding layer, the diamond crystals have self-shaped crystal shapes, and the gap filler is formed by non-stick paint and arranged in gaps between the diamond crystals and adjacent diamond crystals. The substrate is positioned on the metal bonding layer; the sum of the first average thickness of the metal bonding layer and the second average thickness of the gap filler is smaller than the screening particle size of the diamond crystals. The surface, making contact with food, of the cooking utensil is provided with the diamond non-stick surface. The gap filler with excellent non-stick property is filled in the gap between the diamond crystals, so that food materials are prevented from sticking to the gap between the diamond crystals, and the non-stick property of the whole diamond non-stick surface can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of kitchenware, and in particular to a safer, more reliable and more durable diamond non-stick surface and a cooking utensil applied thereon. Background Art

[0002] During the cooking process in the kitchen, the lipophilicity of diamonds causes the diamond surface to automatically be in a highly passivated state, making it non-stick.

[0003] The thermal conductivity of diamond is very high. Although it varies with temperature, grain size, crystal shape and chemical composition, it is generally between 900 and 2320 W / mK (RT), which is one of the highest among known substances. The thermal conductivity of pure copper is only 401 W / mK (RT). Therefore, when diamond is used in cooking utensils, it can heat evenly, cook ingredients quickly, and save energy consumption for cooking and heating.

[0004] Diamond has an extremely high hardness and is almost invulnerable to scratches and wear. Diamond is also extremely chemically inert and is not corroded by any acid or alkali below 500°C. Therefore, diamond is undoubtedly the ultimate non-stick cookware coating material.

[0005] The chemical vapor deposition (CVD) technology for diamond coating has been developed for decades, but it has not been able to achieve large-scale commercial application. The main reason is that the adhesion between the chemical vapor deposition diamond coating and the substrate is weak, and the production cost of large-area chemical vapor deposition diamond coating is extremely high.

[0006] In contrast, the world currently consumes more than 3,500 metric tons of high-pressure, high-temperature (HPHT) synthetic diamonds each year, most of which are used as superabrasives for cutting and grinding, from rough cutting of stone and cement to ultra-precision processing of electronic ceramics and semiconductor wafers.

[0007] See also Figure 1 A scanning electron microscope (SEM) photo of a saw-grade diamond crystal synthesized by the high pressure and high temperature method. As shown in the photo, HPHT synthetic diamonds with complete crystal shape usually have a euhedral shape, and the surface is composed of clear and smooth crystal facets.

[0008] The particle size of commercial HPHT synthetic diamond crystals can range from 38 μm (US ANSI sieve 400 mesh) to 1000 μm (US ANSI sieve 18 mesh).

[0009] See also Figure 2The scanning electron microscope (SEM) photo shows the morphology of diamond powder. Diamond powder usually refers to diamond fine powder with a particle size of less than 54μm. Diamond powder does not have a self-morphic crystal shape. It is mainly made of low-quality HPHT synthetic diamonds that are crushed and ground. Therefore, its shape is irregular, similar to broken glass, and its surface is rough with many sharp corners and recesses.

[0010] Using mass-produced HPHT synthetic diamonds to make non-stick cookware coatings is a feasible method. U.S. Patent No. 6,514,605 ​​discloses a device, the device comprising: a substrate and a diamond-tiled coating formed on the substrate, the coating comprising a ceramic adhesive containing enamel and a plurality of mutually contacting diamond particles bonded to the ceramic adhesive to form an exposed diamond-tiled surface. At least 40% of the exposed surface of the device is diamond, and the maximum size of the diamond particles is less than or equal to 50 μm and greater than 0.01 μm.

[0011] The diamond veneer surface in the above patent document has the following problems:

[0012] The first is that diamond particles are distributed on a substrate surface. There must be gaps between diamond particles. If the material in the gap does not have non-stick properties, the cooked ingredients will stick to the gaps. In the diamond veneer surface in the above patent document, about 50% of the exposed surface is made of enamel material that does not have non-stick properties, which will greatly reduce the non-stick properties of the overall diamond veneer surface.

[0013] The second is that the diamond particles used in the above patent documents are diamond micropowders with smaller particle sizes. Please refer to Figure 2 The surface of diamond particles is rough and irregular in shape. When they come into contact with food, the chance of mechanical interlocking increases greatly, which will actually reduce the non-stick properties of diamond crystals.

[0014] Third, in the above patent documents, ceramic paint materials are used as adhesives for diamond particles. Since ceramic adhesives are very brittle and have weak bonding force with diamonds, they are easily broken under mechanical stress, causing the bonded diamond particles to fall off.

[0015] Therefore, the anti-sticking and non-sticking properties of the existing diamond veneer surface still need to be improved, and the bonding strength between the diamond particles and the substrate also needs to be further improved. How to solve the above problems has become the subject of improvement of the present invention. Summary of the invention

[0016] The object of the present invention is to provide a diamond non-stick surface having excellent non-stick properties and excellent bonding strength between diamond and substrate.

[0017] Another object of the present invention is to provide a cooking utensil, the food contact surface of which has the diamond non-stick surface of the present invention.

[0018] In order to solve the above problems and achieve the purpose of the present invention, the technical means of the present invention is realized as follows: a diamond non-stick surface, the diamond non-stick surface having a metal substrate and a diamond non-stick surface layer; the diamond non-stick surface layer is attached to the metal substrate and comprises a metal bonding layer, a plurality of diamond crystals and a gap filler, the diamond crystals are bonded to the metal substrate through the metal bonding layer, and the diamond crystals have an eumorphic crystal shape, the gap filler is formed by a non-stick coating, is arranged in the gap between the diamond crystal and the adjacent diamond crystal, and is located on the metal bonding layer; the sum of the first average thickness of the metal bonding layer and the second average thickness of the gap filler is less than the screening particle size of the diamond crystal.

[0019] Furthermore, the eumorphic crystal shape of the diamond crystal is a hexaoctahedral crystal.

[0020] Furthermore, the metal bonding layer is combined and fixed to each of the diamond crystals by brazing.

[0021] Furthermore, the particle size of the diamond crystals is in accordance with the American Standards Association standard, with a sieve mesh of 230 / 270 mesh to 20 / 25 mesh and a sieved particle size of 53 μm to 710 μm.

[0022] Furthermore, the first average thickness of the metal bonding layer refers to the average value of the thickness of the metal bonding layer at the middle position of two adjacent diamond crystals is 20 μm to 500 μm;

[0023] The second average thickness of the gap filler refers to an average value of the thickness of the gap filler at the middle position of two adjacent diamond crystals, which is 12 μm to 150 μm.

[0024] Furthermore, the particle size of the diamond crystals is in accordance with the American Standards Association standard, with a sieve mesh ranging from 170 / 200 mesh to 25 / 30 mesh, and a sieved particle size ranging from 75 μm to 600 μm.

[0025] Furthermore, the first average thickness of the metal bonding layer refers to the average value of the thickness of the metal bonding layer at the middle position of two adjacent diamond crystals is 25 μm to 420 μm;

[0026] The second average thickness of the gap filler refers to an average value of the thickness of the gap filler at the middle position of two adjacent diamond crystals being 20 μm to 120 μm.

[0027] Furthermore, the metal bonding layer contains 5wt% to 26wt% of chromium; and the metal substrate is stainless steel.

[0028] Furthermore, the metal bonding layer contains 1.5 wt % to 20 wt % of titanium.

[0029] Furthermore, the non-stick coating of the gap filler is one of fluorocarbon resin coating, silicone resin coating and sol-gel ceramic coating.

[0030] Another technical means of the present invention is achieved by providing a cooking utensil, wherein the surface of the cooking utensil that contacts food has the above-mentioned diamond non-stick surface.

[0031] After adopting the above technical solution, the present invention has the following benefits compared with the prior art:

[0032] First point: The present invention fills the gaps between diamond crystals with gap fillers having excellent non-stick properties to prevent food from sticking to the gaps between diamond crystals, which can greatly improve the non-stick properties of the entire diamond non-stick surface.

[0033] Second point: The present invention uses diamond crystals with smooth crystal surfaces and hexahedral crystal shapes, which can effectively reduce the chance of mechanical interlocking when the diamond crystals come into contact with food, thereby enhancing the non-stick effect of the diamond crystals.

[0034] Third point: The metal bonding layer of the present invention uses an active brazing alloy containing chromium or titanium, which can react with the surface of diamond crystals to form carbides and metallurgically bond with the metal substrate, greatly improving the bonding strength to the diamond crystals. Even under extremely high mechanical stress, the diamond crystals will not fall off. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope image of a saw-grade diamond crystal.

[0036] Figure 2 This is a scanning electron microscope photo of diamond powder.

[0037] Figure 3 Schematic diagram of the manufacturing process of the diamond non-stick surface of the present invention.

[0038] Figure 4a A cross-sectional diagram of the manufacturing process of the diamond non-stick surface of the present invention Figure 1 .

[0039] Figure 4b A cross-sectional diagram of the manufacturing process of the diamond non-stick surface of the present invention Figure 2 .

[0040] Figure 4cA cross-sectional diagram of the manufacturing process of the diamond non-stick surface of the present invention Figure 3 .

[0041] Figure 4d Schematic diagram 4 of the cross-section of the manufacturing process of the diamond non-stick surface of the present invention.

[0042] Figure 4e A cross-sectional diagram of the manufacturing process of the diamond non-stick surface of the present invention Figure 5 .

[0043] Figure 4f Schematic diagram 6 of the cross-section of the manufacturing process of the diamond non-stick surface of the present invention.

[0044] Figure 5 It is a three-dimensional schematic diagram of the cooking utensil of the present invention.

[0045] Description of reference numerals:

[0046] 1 Metal substrate

[0047] 2 Diamond does not stick to the surface

[0048] 21 Metal bonding layer

[0049] 22 Diamond Crystal

[0050] 23 Gap filler

[0051] 100 Diamond Non-Stick Surface

[0052] 200 Cooking utensils

[0053] B The first average thickness

[0054] G Second average thickness DETAILED DESCRIPTION

[0055] The technical solution of the present invention is described clearly and completely below by way of examples in conjunction with the accompanying drawings of the specification. Obviously, the described implementation is only a part of the implementation of the present invention, not all of the implementations. Based on the implementation of the present invention, all other implementations obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] like Figures 3 to 5As shown in the figure, a diamond non-stick surface is shown, wherein the diamond non-stick surface 100 has a metal substrate 1 and a diamond non-stick surface layer 2; the diamond non-stick surface layer 2 is attached to the metal substrate 1, and comprises a metal bonding layer 21, a plurality of diamond crystals 22 and a gap filler 23, wherein the diamond crystals 22 are bonded to the metal substrate 1 through the metal bonding layer 21, and the diamond crystals 22 have a self-morphous crystal shape, and the gap filler 23 is formed by a non-stick coating, and is disposed in the gap between the diamond crystals 22 and the adjacent diamond crystals 22, and is located on the metal bonding layer 21; the sum of the first average thickness B of the metal bonding layer 21 and the second average thickness G of the gap filler 23 is less than the sieved particle size D of the diamond crystals 22. S .

[0057] See also Figure 3 and Figure 4a First, step 1 S1: provide a metal substrate 1. As the metal substrate 1 of the present invention, one of carbon steel, stainless steel, cast iron, copper, copper alloy, titanium and titanium alloy can be selected. Carbon steel and stainless steel are preferably used. In step 1 S1, if necessary, the surface of the metal substrate 1 can be roughened. The roughening treatment of the surface can be carried out by any method, including but not limited to: acid chemical etching, alkaline chemical etching, mechanical grinding or sandblasting.

[0058] See also Figure 3 and Figure 4b , step two S2: placing a material for forming a metal bonding layer 21 on the surface of the metal substrate 1 .

[0059] The placement method can be determined according to the form (eg, foil, powder, wire, etc.) of the brazing alloy used to form the metal bonding layer 21. The brazing alloy in foil form can be selected and cut into any shape and temporarily fixed on the surface of the metal substrate 1 with an adhesive.

[0060] Preferably, a powdered brazing alloy is used, and an organic adhesive and a solvent can be added to the alloy powder to prepare a flexible pad, solder paste or solder paint. The flexible pad can be easily processed into any desired shape and then temporarily fixed on the surface of the metal substrate 1 with an adhesive. The solder paste can be applied to the surface of the metal substrate 1 by screen printing or brushing; and the solder paint can be applied to the surface of the metal substrate 1 by spraying, screen printing, brushing, etc.

[0061] Preferably, the brazing alloy powder is prepared into a welding paint, which is then applied on the surface of the metal substrate 1 by spraying.

[0062] In step 2 S2, the metal bonding layer 21 that can be used in the present invention mainly contains active brazing alloys containing strong carbide-forming elements such as chromium (Cr), niobium (Nb), tantalum (Ta), vanadium (V), titanium (Ti), zirconium (Zr), etc., especially active brazing alloys containing chromium (Cr) or titanium (Ti). The metal bonding layer 21 formed by the active brazing alloy can react with carbon on the surface of the diamond crystal 22 to form a strong chemical bond to generate very stable carbides, such as Cr3C2, Cr7C3, NbC, TaC, V4C3, TiC, ZrC, and can form a metallurgical bonding with the metal substrate 1, greatly improving the bonding strength to the diamond.

[0063] The Cr-containing brazing alloy preferably used for the metal bonding layer 21 of the present invention includes, but is not limited to, the commercial Cr-containing brazing alloy compositions listed in Table 1.

[0064] Table 1 Composition of commercial chromium-containing brazing alloys

[0065]

[0066]

[0067] Advantageously, the composition of the metal bonding layer 21 used in the present invention preferably contains 5wt% to 26wt% of chromium (Cr); and the matching metal substrate 1 is preferably stainless steel.

[0068] Titanium (Ti)-containing brazing alloys preferably used in the metal bonding layer 21 of the present invention include, but are not limited to, commercial titanium-containing brazing alloy compositions listed in Table 2.

[0069] Table 2 Composition of commercial titanium-containing brazing alloys

[0070]

[0071] Advantageously, the composition of the metal bonding layer 21 used in the present invention preferably contains 1.5wt% to 20wt% of titanium (Ti); and the matching metal substrate 1 is not particularly limited and has high versatility.

[0072] See also Figure 3 and Figure 4c Step three S3: distributing diamond crystals 22 on the material used to form the metal bonding layer 21.

[0073] There is no particular limitation on the method of distributing the diamond crystals 22, and any appropriate method may be used. A screen may be used to evenly distribute the diamond crystals 22, or a screen, a silk screen or other template may be used to distribute the diamond crystals 22 into any form. For ease of operation, an adhesive, such as a pressure-sensitive adhesive, may be used to temporarily position the diamond crystals 22 on the material used to form the metal bonding layer 21.

[0074] Advantageously, the diamond crystal 22 of the present invention is mainly a diamond with an eumorphic crystal shape. If the diamond crystal shape is complete, it usually contains two crystal faces, namely, a cubic face and an octahedral face. As the growth rate perpendicular to the two crystal faces increases or decreases, the size of the cubic face and the octahedral face will increase or decrease accordingly, forming a series of cubo-octahedron crystal shapes.

[0075] The morphology of HPHT synthetic diamonds is usually a variety of hexahedral crystals composed of small crystal faces of cubic faces and octahedral faces.

[0076] Advantageously, the diamond crystal 22 used in the present invention may have a hexaoctahedral crystal shape.

[0077] The particle size grading of HPHT synthetic diamonds in the commercial market is generally done by sieving using sieves.

[0078] Advantageously, the particle size of the diamond crystals 22 of the present invention can be selected according to the American Institute of Standards and Technology (ANSI) specifications, with a mesh size of 230 / 270 to 20 / 25, for example: 230 / 270, 200 / 230, 170 / 200, 140 / 170, 120 / 140, 100 / 120, 80 / 100, 70 / 80, 60 / 70, 50 / 60, 45 / 50, 40 / 45, 35 / 40, 30 / 35, 25 / 30 and 20 / 25.

[0079] Advantageously, the particle size of the diamond crystals 22 used in the present invention preferably uses the American Standards Institute (ANSI) specifications, and the mesh is 170 / 200 mesh to 25 / 30 mesh, for example: 170 / 200 mesh, 140 / 170 mesh, 120 / 140 mesh, 100 / 120 mesh, 80 / 100 mesh, 70 / 80 mesh, 60 / 70 mesh, 50 / 60 mesh, 45 / 50 mesh, 40 / 45 mesh, 35 / 40 mesh, 30 / 35 mesh and 25 / 30 mesh.

[0080] In general, there is no limit on the upper limit of the particle size of the diamond crystals 22 under the concept of the present invention. However, in business, the larger the particle size, for example, greater than 20 mesh, the cost of diamonds will rise sharply and become less practical. If diamond crystals 22 with smaller particle sizes are used, for example, less than 270 mesh, the crystal shape of the diamonds will be less complete and irregular, and the non-stick performance will also be reduced.

[0081] According to the present invention, the screening particle size D of the diamond crystal 22 is S , defined as the square mesh width of the sieve under each particle size number, expressed in μm.

[0082] For example: The screening particle size D of 230 / 270 mesh diamond crystal 22 S is the square mesh width of the 270 mesh screen, i.e. the screening particle size D of the 230 / 270 mesh diamond crystal 22 S It is 53μm.

[0083] Advantageously, the particle size of the diamond crystals 22 used in the present invention can be selected from the sieve particle size D S It is 53μm to 710μm, for example: 53μm, 63μm, 75μm, 90μm, 106μm, 125μm, 150μm, 180μm, 212μm, 250μm, 300μm, 355μm, 425μm, 500μm, 600μm and 710μm.

[0084] More advantageously, the particle size of the diamond crystals 22 used in the present invention may also be a sieve particle size D S It is 75μm to 600μm, for example: 75μm, 90μm, 106μm, 125μm, 150μm, 180μm, 212μm, 250μm, 300μm, 355μm, 425μm, 500μm and 600μm.

[0085] See also Figure 3 and Figure 4d Step 4 S4: brazing the diamond crystal 22 on the surface of the metal substrate 1. That is, the metal substrate 1, the brazing alloy and the diamond crystal 22 that have been assembled together are brazed.

[0086] In order to prevent the graphitization of diamond during high temperature brazing and to avoid oxidation of the brazing alloy and the metal substrate 1, the selection of the heating atmosphere is important.

[0087] The heating method for brazing can be a reducing atmosphere furnace, an inert gas atmosphere furnace or a vacuum furnace.

[0088] Preferably, vacuum furnace brazing is used, and the vacuum pressure can be from about 0.1 Pa to about 0.0001 Pa. The optimal brazing temperature is usually at a temperature slightly higher than the liquidus temperature of the brazing alloy to promote the flow and wetting of the brazing alloy to the diamond and metal substrate 1, for example, see the brazing temperature ranges of various brazing alloy compositions in Tables 1 and 2.

[0089] Regarding the heating cycle of the heating furnace during brazing, a person skilled in the art who is familiar with the field can select an appropriate value according to actual needs.

[0090] See also Figure 4d After the brazing step, the diamond crystal 22 is brazed to the surface of the metal substrate 1. During the melting process of the brazing alloy, the bottom and side surfaces of the diamond crystal 22 will be wetted by the alloy to form a unique wetting shape, and finally a concave surface is formed on the surface of the metal bonding layer 21, that is, the metal bonding layer 21 has a lowest point in the middle of two adjacent diamond crystals 22.

[0091] The present invention defines that the thickness of the metal bonding layer 21 refers to the thickness of the metal bonding layer 21 at the middle position of two adjacent diamond crystals 22, and the first average thickness B of the metal bonding layer 21 refers to the average value of the thickness of the metal bonding layer 21 at the middle position of two adjacent diamond crystals 22.

[0092] The thickness of the metal bonding layer 21 can be obtained by cross-sectional observation using an optical microscope or a scanning electron microscope (SEM) and microscopic image measurement.

[0093] Although not shown in the figure, according to the present invention, the thickness of the metal bonding layer 21 at the middle position of 20 adjacent diamond crystals 22 is randomly measured on the cross-section of the diamond non-stick surface 100, and then the average value of the 20 measured thicknesses is used as the first average thickness B of the metal bonding layer 21.

[0094] Since the brazing alloy has good wettability to diamond, it will adhere to the surface of the diamond and form a unique wetting profile, thereby increasing the contact area between the brazing alloy and the diamond crystal 22 and forming a very stable bond.

[0095] Therefore, the thickness of the metal bonding layer 21 required by the present invention can be within a range of about 0.2 to about 0.7 times the sieve particle size D of diamond. S , and can form a stable bond with the diamond crystal 22.

[0096] Advantageously, the first average thickness B of the metal bonding layer 21 of the present invention is 20 μm to 500 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm. m, 180μm, 185μm, 190μm, 195μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 33 0μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm, 400μm, 410μm, 420μm, 430μm, 440μm, 450μm, 460μm, 470μm, 480μm, 490μm and 500μm.

[0097] More advantageously, the first average thickness B of the metal bonding layer 21 of the present invention is preferably 25 μm to 420 μm, for example, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm. m, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 27 0μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm, 400μm, 410μm and 420μm.

[0098] If the thickness of the metal bonding layer 21 is too large, the brazing alloy may flow over the surface of the diamond crystal 22 and cover it with a layer of metal; if the thickness of the metal bonding layer 21 is too small, the bonding strength to the diamond crystal 22 may be relatively poor.

[0099] See also Figure 3 and Figure 4eStep 5 S5: dispose a gap filler 23 in the gap between the diamond crystals 22 and the diamond crystals 22, and located on the metal bonding layer 21. The gap filler 23 is formed by a non-stick coating.

[0100] Advantageously, the non-stick coatings that can be used in the present invention as the gap filler 23 include fluorocarbon resin coatings, silicone resin coatings and sol-gel ceramic coatings.

[0101] Advantageously, the fluorocarbon resin coating that can be used in the present invention is a fluorocarbon resin coating that is conventionally used for non-stick coatings, and preferably polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), fluorinated ethylene propylene (FEP) and mixtures thereof.

[0102] Preferably, the fluorocarbon resin coating may further contain reinforcing fillers and / or pigments.

[0103] The composition of the fluorocarbon resin coating mentioned in the present invention is not a critical factor. There are many fluorocarbon resin coating compositions traditionally used for non-stick coatings that can be used as the gap filler 23 of the present invention.

[0104] Furthermore, the fluorocarbon resin coating preferably comprises a multi-layer coating structure, such as a primer and at least one topcoat.

[0105] More preferably, the fluorocarbon resin coating may also contain one or more heat-resistant adhesive resins, such as polyamide-imide resin (PAI), polyimide resin (PI), polyethersulfone resin (PES), polyphenylene sulfide resin (PPS), and polyetheretherketone resin (PEEK).

[0106] Advantageously, the silicone resin coating that can be used in the present invention is a silicone resin coating that is conventionally used in non-stick coatings. Preferably, the silicone resin coating can further contain pigments and / or fillers.

[0107] For example: carbon black, graphite, titanium dioxide (TiO2), iron oxide (Fe2O3, Fe3O4), silicon dioxide (SiO2), aluminum oxide (Al2O3), aluminum powder, glass powder, mica, calcium carbonate (CaCO3) or silicon carbide (SiC).

[0108] The composition of the silicone resin coating mentioned in the present invention is not a critical factor. There are many silicone resin coating compositions traditionally used for non-stick coatings that can be used as the gap filler 23 of the present invention.

[0109] Advantageously, the sol-gel ceramic coating that can be used in the present invention is a sol-gel ceramic coating that is conventionally used in non-stick coatings.

[0110] The sol-gel ceramic coating preferably used in the present invention is a non-stick ceramic coating containing silicon (Si) in any component.

[0111] Furthermore, the sol-gel ceramic coating may further contain pigments and / or fillers.

[0112] For example: titanium dioxide (TiO2), iron oxide (Fe2O3, Fe3O4 ) , mica, silicon dioxide (SiO2), aluminum oxide (Al2O3) or silicon carbide (SiC).

[0113] The composition of the sol-gel ceramic coating mentioned in the present invention is not a critical factor. There are many sol-gel ceramic coating compositions conventionally used for non-stick coatings that can be used as the gap filler 23 of the present invention.

[0114] The gap filler 23 can be configured by various conventional coating methods, including, for example, spraying, brushing, rolling, showering, dipping or spin coating.

[0115] A preferred method is to configure the gap filler 23 by spraying.

[0116] After the gap filler 23 is disposed, it is then dried and baked to allow the gap filler 23 to solidify and bond with the metal adhesive layer 21. The temperature and time of drying and baking will vary according to the composition and thickness of the gap filler 23. Technicians familiar with the non-stick coating process know the temperature and time of drying and baking required for the composition and thickness of various gap fillers 23.

[0117] See also Figure 4e In the present invention, a gap filler 23 is arranged in the gap between diamond crystals 22, and is dried and baked to solidify the gap filler 23; a concave surface is formed on the surface of the solidified gap filler 23, that is, the gap filler 23 has a lowest point in the middle of two adjacent diamond crystals 22.

[0118] The present invention defines that the thickness of the gap filler 23 refers to the thickness of the gap filler 23 at the middle position of two adjacent diamond crystals 22, and the second average thickness G of the gap filler 23 refers to the average value of the thickness of the gap filler 23 at the middle position of two adjacent diamond crystals 22.

[0119] The thickness of the gap filler 23 can be obtained by cross-sectional observation using an optical microscope or a scanning electron microscope (SEM) and microscopic image measurement.

[0120] Although not shown in the figure, according to the present invention, the thickness of the gap filler 23 at the middle position of 20 adjacent diamond crystals 22 is randomly measured on the cross-section of the diamond non-stick surface 100, and then the average value of the 20 measured thicknesses is used as the second average thickness G of the gap filler 23.

[0121] Advantageously, in the present invention, the sum of the first average thickness B of the metal bonding layer 21 and the second average thickness G of the gap filler 23 is less than the sieve particle size D of the plurality of diamond crystals 22. S Such a design can make the surface concave surface of the gap filler 23 lower than the adjacent diamond crystal 22 .

[0122] When the diamond non-stick surface 100 of the present invention is scraped or subjected to abrasive force during cooking or cleaning, only the high points of the diamond crystals 22 will be subjected to mechanical stress. The gap fillers 23 located at the low points of the gaps between the diamond crystals 22 will be protected by the diamond crystals 22 from being damaged or worn.

[0123] Advantageously, the second average thickness G of the gap filler 23 of the present invention is 12 μm to 150 μm, for example, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm. , 50μm, 52μm, 54μm, 56μm, 58μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm and 150μm.

[0124] More advantageously, the second average thickness G of the gap filler 23 in the present invention is preferably 20μm to 120μm, for example: 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm, 50μm, 52μm, 54μm, 56μm, 58μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm and 120μm.

[0125] If the thickness of the gap filler 23 is too large, the gap filler 23 may cover the diamond surface; if the thickness of the gap filler 23 is too small, the non-stick property may be poor.

[0126] like Figure 4e As shown, during the process of configuring the gap filler 23 , excess gap filler 23 will be deposited on the top of the diamond crystal 22 .

[0127] Next, see Figure 3 In step six S6: remove the excess gap filler 23 on the top of the diamond crystal 22. Any well-known method can be used, such as brushing, scrubbing, brushing with a grinding disc or mechanical grinding, polishing.

[0128] See also Figure 4f The top of the diamond crystal 22 has been cleaned to expose the bright crystal surface. Advantageously, the diamond crystal 22 used in the present invention is a diamond particle with a hexaoctahedral crystal form, and the outer shape is composed of a smooth crystal growth surface with a small surface roughness.

[0129] Furthermore, the hexaoctahedral diamond particles have good roundness. Therefore, during the cooking process, the diamond non-stick surface 100 of the present invention will not hinder the release of the contacted food, and the overall non-stick ability is greatly improved.

[0130] like Figure 5 As shown in the figure, a cooking utensil is shown, wherein the surface of the cooking utensil 200 that contacts food has a diamond non-stick surface 100 as in the present invention.

[0131] Among them, through the setting of the diamond non-stick surface 100, the cooking utensil 200 can obtain better non-stick properties, allowing consumers to use it with peace of mind and safety. Moreover, compared with existing non-stick cookware, there are almost no restrictions on its use. When cooking, it is not limited to silicone spatulas and wooden spatulas, and ordinary iron spatulas can also be used. It is more convenient to clean, can be easily used and cleaned, has no learning cost, and is conducive to promotion.

[0132] Secondly, the cooking utensil 200 is one of a frying pan, a European wok, a Chinese wok, a barbecue frying pan, a flat frying pan, a pancake pan, a BBQ pan, a baking pan, a stew pot, a Dutch oven, a stew pot, a soup pot or a flat iron pan.

[0133] Furthermore, the cooking utensil 200 generally further includes at least one handle disposed on the outer surface of the edge.

[0134] In the following embodiments, the first average thickness B of the metal bonding layer 21 and the second average thickness G of the gap filler 23 are estimated by cross-sectional observation using a scanning electron microscope (SEM).

[0135] First, the thickness of the metal bonding layer 21 at the middle positions of 20 adjacent diamond crystals 22 on the cross section of the diamond non-stick surface 100 is randomly measured, and then the average value of the 20 measured thicknesses is taken as the first average thickness B of the metal bonding layer 21 .

[0136] Next, the thickness of the gap filler 23 at the middle position of 20 adjacent diamond crystals 22 is randomly measured, and then the average value of the 20 measured thicknesses is taken as the second average thickness G of the gap filler 23 .

[0137] Embodiment 1:

[0138] An 8-inch stainless steel baking pan sold on the market was used as the metal substrate. The inner surface of the baking pan was first degreased with acetone, then roughened by sandblasting, then washed with water, and finally dried with hot air.

[0139] The material of the metal bonding layer is a BNi-2 brazing alloy, which has the following components: chromium (6-8wt%), boron (2.75-3.50wt%), silicon (4-5wt%), iron (2.5-3.5wt%) and nickel (balance), and the particle size is less than 325 mesh.

[0140] In the brazing alloy powder, water-based acrylic resin and deionized water solvent are added to prepare welding paint, and then the welding paint is sprayed on the inner surface of the stainless steel baking tray with a gravity spray gun (nozzle diameter is 0.5mm) and the spraying pressure is 0.25MPa, and then hot air is dried at 80℃ for 15 minutes. Controlling the spraying thickness of the welding paint can adjust the first average thickness of the metal bonding layer. The synthetic diamond model used is HSD90 (manufactured by Huanghe Cyclone Company), the particle size of the diamond is the American Standards Association (ANSI), the mesh is 20 / 25 mesh, and the crystal shape of the diamond is hexaoctahedron.

[0141] First, apply pressure-sensitive adhesive FB49 (manufactured by 3M) on the dry solder paint surface, then sprinkle diamond crystals, and densely adhere a layer of diamonds through the pressure-sensitive adhesive. Then put the baking tray into a vacuum furnace for high vacuum brazing. The vacuum pressure is about 0.01Pa, the brazing temperature is 1010℃, and the constant temperature time is 10 minutes. After the brazing is completed, cool it with the furnace. The gap filler used is fluorocarbon grease coating, which includes a black primer (primer) 420G-703 (manufactured by Chemous) and a PFA topcoat (topcoat) 858G-210 (manufactured by Chemous).

[0142] The paint was sprayed with a gravity spray gun (nozzle diameter 0.5mm) at a spray pressure of 0.2MPa. The primer was dried at 220℃ for 10 minutes, the surface paint was dried at 150℃ for 10 minutes, and then the paint was baked in an air oven at 400℃ for 15 minutes.

[0143] After multiple spraying, the required second average thickness of the gap filler can be obtained. Then, the diamond crystal surface is ground in water with a grinding sheet, the trade name is Scotch-Brite 96S-5M (manufactured by 3M Company), and the excess coating sprayed on the top of the diamond crystal is removed to expose the bright crystal surface.

[0144] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0145] Embodiments 2 and 3:

[0146] An 8-inch stainless steel baking pan sold on the market was used as a metal substrate, and a diamond non-stick surface was prepared in the same manner as in Example 1.

[0147] The synthetic diamond model used in Example 2 is HWD92 (manufactured by Huanghe Cyclone Company), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a sieve size of 40 / 45 mesh.

[0148] The synthetic diamond model used in Example 3 is SDB1100 (manufactured by Element Six), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a sieve size of 25 / 30 mesh.

[0149] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0150] Embodiment 4:

[0151] An 8-inch carbon steel frying pan sold on the market was used as the metal substrate. The inner surface of the frying pan was first degreased with acetone, then roughened by sandblasting, then washed with water, and finally dried with hot air.

[0152] The material of the metal bonding layer is a CuSnTi brazing alloy, which has the following components: titanium (9-11 wt%), tin (18-20 wt%) and copper (balance), and the particle size is less than 300 meshes.

[0153] In the brazing alloy powder, water-based acrylic resin and deionized water solvent are added to prepare welding paint, and then the welding paint is sprayed on the inner surface of the carbon steel frying pan with a gravity spray gun (nozzle diameter is 0.5mm) and the spraying pressure is 0.25MPa, and then hot air drying is carried out at 80℃ for 15 minutes. Controlling the spraying thickness of the welding paint can adjust the first average thickness of the metal bonding layer. The synthetic diamond model used is HFD-D (manufactured by Huanghe Cyclone Company), the particle size of the diamond is the American Standards Association (ANSI), the mesh is 120 / 140 mesh, and the crystal shape of the diamond is hexaoctahedron.

[0154] First, apply pressure-sensitive adhesive FB49 (manufactured by 3M) on the dry soldering paint surface, and then sprinkle diamond crystals to densely adhere a layer of diamonds through the pressure-sensitive adhesive. Then put the frying pan into a vacuum furnace for high vacuum brazing, the vacuum pressure is about 0.01Pa, the brazing temperature is 920℃, the constant temperature time is 20 minutes, and after the brazing is completed, it is cooled in the furnace. The following production method is the same as that of Example 1.

[0155] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0156] Embodiment five:

[0157] An 8-inch stainless steel baking pan sold on the market was used as a metal substrate, and a diamond non-stick surface was prepared in the same manner as in Example 1.

[0158] The synthetic diamond model used is HWD-92 (manufactured by Huanghe Cyclone Company), the particle size of the diamond is the American Standards Association (ANSI), and the mesh size is 45 / 50 mesh. The gap filler used is silicone resin paint, model PAOFLON9666-161 (manufactured by Baokun Chemical Company), which contains carbon black and aluminum powder pigments. The paint is sprayed with a gravity spray gun (nozzle diameter is 0.5mm) and the spraying pressure is 0.2MPa. After spraying, it is dried at 150℃ hot air for 10 minutes, and then baked in an air furnace at 280℃ for 15 minutes. After multiple spraying, the required second average thickness of the gap filler can be obtained.

[0159] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0160] Embodiment six to eight:

[0161] An 8-inch carbon steel frying pan sold on the market was used as the metal substrate, and the diamond non-stick surface was made in the same manner as in Example 4.

[0162] The synthetic diamond model used in Example 6 is HFD-D (manufactured by Huanghe Cyclone Company), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a sieve size of 140 / 170 mesh.

[0163] The synthetic diamond model used in Example 7 is HFD-D (manufactured by Huanghe Cyclone Company), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a mesh size of 100 / 120.

[0164] The synthetic diamond model used in Example 8 is PDA999 (manufactured by Element Six), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a sieve size of 80 / 90 mesh.

[0165] The gap filler used is silicone resin coating, and the manufacturing method is the same as that of the fifth embodiment.

[0166] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0167] Embodiment nine:

[0168] An 8-inch carbon steel frying pan sold on the market was used as the metal substrate, and the diamond non-stick surface was made in the same manner as in Example 4.

[0169] The synthetic diamond model used is PDA999 (manufactured by Element Six), and the particle size of the diamond is the American Standards Association (ANSI), with a mesh size of 170 / 200. The gap filler used is a sol-gel ceramic coating, model NC-9168-4711 (manufactured by Baokun Chemical Company), which is a non-stick ceramic coating containing silica sol. The coating is sprayed with a gravity spray gun (nozzle diameter is 0.5mm) and the spraying pressure is 0.2MPa. After spraying, it is dried at 150℃ hot air for 10 minutes, and then baked in an air furnace at 280℃ for 15 minutes.

[0170] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0171] Embodiment ten:

[0172] An 8-inch stainless steel baking pan sold on the market was used as a metal substrate, and a diamond non-stick surface was prepared in the same manner as in Example 1.

[0173] The synthetic diamond model used is HFD-D (manufactured by Huanghe Cyclone Company), the particle size of the diamond is the American Standards Association (ANSI), and the mesh size is 230 / 270. The gap filler used is sol-gel ceramic coating, and the preparation method is the same as that of Example 9.

[0174] The first average thickness of the metal bonding layer of the diamond non-stick surface and the second average thickness of the gap filler obtained are shown in Table 3.

[0175] Comparative Examples 1 to 3:

[0176] An 8-inch stainless steel baking pan sold on the market was used as the metal substrate, and a diamond non-stick surface was produced in the same manner as in Example 1, except that no gap filler was arranged in the gaps between the diamond crystals.

[0177] The synthetic diamond model used in Comparative Example 1 is PDA446 (manufactured by Element Six), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a mesh size of 170 / 200.

[0178] The synthetic diamond model used in Comparative Example 2 is SDB1100 (manufactured by Element Six), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a sieve size of 35 / 40 mesh.

[0179] The synthetic diamond model used in Comparative Example 3 is PDA999 (manufactured by Element Six), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a mesh size of 80 / 90.

[0180] Comparative Examples 4 and 5:

[0181] An 8-inch carbon steel frying pan sold on the market was used as the metal substrate, and a diamond non-stick surface was produced in the same manner as in Example 4, except that no gap filler was arranged in the gaps between the diamond crystals.

[0182] The synthetic diamond model used in Comparative Example 4 is W3.5 (manufactured by Yuefeng Diamond Company), the particle size of the diamond is the American Institute of Standards and Technology (ANSI), and the sieve size is about 6000 mesh.

[0183] The synthetic diamond model used in Comparative Example 5 is HFD-D (manufactured by Huanghe Cyclone Company), and the particle size of the diamond is the American Institute of Standards and Technology (ANSI), with a mesh size of 230 / 270.

[0184] Non-stick test:

[0185] Heat a baking tray or frying pan to 150°C with an electric heating plate. Measure the temperature of the pan surface with a contact thermocouple thermometer. Do not use or spray cooking oil on the pan surface. Add about 50 ml of egg liquid and heat for 2 minutes.

[0186] The non-stick performance is assessed based on how well the egg sticks to the pan, using a 5-point scale.

[0187] 5 points: The egg can be peeled completely.

[0188] 4 points: Most of the egg can be peeled off, with only a small amount remaining, about 1 cm 2 or less.

[0189] 3 points: The egg is sticky, about 3 to 4 cm 2 Residue.

[0190] 2 points: About 50% of the egg is adhered.

[0191] 1 point: About 75% or more of the egg is adhered.

[0192] See Table 3 for the non-stick test results.

[0193] Table 3 Test results of the embodiments of the present invention and the comparative examples

[0194]

[0195]

[0196]

[0197] The results in Table 3 clearly show that the non-stick properties of Examples 1 to 10 of the diamond non-stick surface of the present invention are much better than those of Comparative Examples 1 to 5. Therefore, the diamond non-stick surface of the present invention is very suitable for use in non-stick cooking utensils.

[0198] Although the content of the present invention has been described in detail by taking the above embodiments as examples, the present invention is not limited to such implementation methods. Those skilled in the art in the technical field to which the present invention belongs should be able to understand and appreciate that various changes and modifications can be made without departing from the spirit and scope of the present invention; for example, the various technical contents illustrated in the above embodiments are combined or changed to form new implementation methods, and such implementation methods are of course regarded as the content of the present invention. Therefore, the scope to be protected in this case also includes the scope of the patent application described later and the scope defined therein.

Claims

1. A diamond non-stick surface, characterized by: The diamond non-stick surface (100) comprises a metal substrate (1) and a diamond non-stick surface layer (2); The diamond non-stick surface layer (2) is attached to the metal substrate (1) and comprises a metal bonding layer (21), a plurality of diamond crystals (22) and a gap filler (23). The diamond crystals (22) are bonded to the metal substrate (1) through the metal bonding layer (21), and the diamond crystals (22) have an eumorphic crystal shape. The gap filler (23) is formed by a non-stick coating, and is arranged in a gap between the diamond crystals (22) and adjacent diamond crystals (22), and is located on the metal bonding layer (21); The sum of the first average thickness (B) of the metal bonding layer (21) and the second average thickness (G) of the gap filler (23) is smaller than the sieved particle size of the diamond crystals (22).

2. The diamond non-stick surface according to claim 1, characterized in that: The eumorphic crystal shape of the diamond crystal (22) is a hexaoctahedral crystal.

3. The diamond non-stick surface according to claim 2, characterized in that: The metal bonding layer (21) is used to bond and fix each of the diamond crystals (22) by means of brazing.

4. The diamond non-stick surface according to claim 3, characterized in that: The particle size of the diamond crystal (22) is in accordance with the American Standards Association standard, with a sieve mesh of 230 / 270 mesh to 20 / 25 mesh, and a sieved particle size of 53 μm to 710 μm.

5. The diamond non-stick surface according to claim 4, characterized in that: The first average thickness (B) of the metal bonding layer (21) refers to the average value of the thickness of the metal bonding layer (21) at the middle position of two adjacent diamond crystals (22) being 20 μm to 500 μm; The second average thickness (G) of the gap filler (23) refers to the average value of the thickness of the gap filler (23) at the middle position of two adjacent diamond crystals (22) being 12 μm to 150 μm.

6. The diamond non-stick surface according to claim 5, characterized in that: The metal bonding layer (21) contains 5wt% to 26wt% of chromium; The metal substrate (1) is stainless steel.

7. The diamond non-stick surface according to claim 6, characterized in that: The non-stick coating of the gap filler (23) is one of a fluorocarbon resin coating, a silicone resin coating and a sol-gel ceramic coating.

8. The diamond non-stick surface according to claim 5, characterized in that: The metal bonding layer (21) contains 1.5 wt% to 20 wt% of titanium.

9. The diamond non-stick surface according to claim 8, characterized in that The non-stick coating of the gap filler (23) is one of a fluorocarbon resin coating, a silicone resin coating and a sol-gel ceramic coating.

10. A cooking utensil, characterized in that: The surface of the cooking utensil (200) that contacts food has the diamond non-stick surface (100) as claimed in claim 1.

Citation Information

Patent Citations

  • Diamond-tiled workpiece for durable surfaces

    US6514605B2